Recent Literature on Wage Theory - Dickinson, Z. C. (Quarterly Journal of Economics, 1934)
Journal Article Recent Literature on Wage Theory Get access Z. C. Dickinson Z. C. Dickinson University of Michigan Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 49, Issue 1, November 1934, Pages 138–146, https://doi.org/10.2307/1883880 Published: 01 November 1934